Knowledge, Attitudes, Self-Efficacy of Children About Prevention of Sexual Violence Against Children - Muhammad Fasya Tisnawan; Linda Suwarni; Selviana Selviana; Vidyastuti Vidyastuti; Widya Lestari (Jurnal Berkala Kesehatan, 2021)
Child sexual violence is a global problem and tends to increase from time to time. The lack of knowledge, attitudes, and self-efficacy in children about the concept of sexual violence is a contributing factor to sexual violence against children. However, data on children's knowledge, attitudes, and self-efficacy regarding the prevention of sexual violence are still limited. This study aimed to describe children's knowledge, attitudes, and self-efficacy towards the prevention of sexual violence and the incidence of sexual violence in children. This research is quantitative with a cross-sectional study approach. The population of this study was children aged 12-17 years in Pontianak City, with a total sample of 396 people. Proportional random sampling was used in six sub-districts in Pontianak City. Data analysis used univariate analysis in the form of percentages. The study results found that 68.9% had poor knowledge of sexual violence against children and its prevention, 55.8% were unsupportive of sexual violence, 47.5% had low self-efficacy in preventing sexual violence, and 56.6% of children had experienced sexual violence. A comprehensive intervention strategy is needed for parents as the first environment known to children to prevent sexual violence against children.